The Mother or the Fetus? 11β-Hydroxysteroid Dehydrogenase Type 2 Null Mice Provide Evidence for Direct Fetal Programming of Behavior by Endogenous Glucocorticoids - Holmes, Megan C. (J Neurosci, 2006)
Low birth weight associates with increased susceptibility to adult cardiometabolic and affective disorders spawning the notion of fetal “programming.” Prenatal exposure to excess glucocorticoids may be causal. In support, maternal stress or treatment during pregnancy with dexamethasone (which crosses the placenta) or inhibitors of fetoplacental 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2), the physiological “barrier” to maternal glucocorticoids, reduces birth weight and programs permanent offspring hypertension, hyperglycemia, and anxiety behaviors. It remains uncertain whether such effects are mediated indirectly via altered maternal function or directly on the fetus and its placenta. To dissect this critical issue, we mated 11β-HSD2(+/−) mice such that each pregnant female produces +/+, +/−, and −/− offspring and compared them with offspring of homozygous wild-type and −/− matings. We show that 11β-HSD2(−/−) offspring of either +/− or −/− mothers have lower birth weight and exhibit greater anxiety than 11β-HSD2(+/+) littermates. This provides clear evidence for the key role of fetoplacental 11β-HSD2 in prenatal glucocorticoid programming.